The Relation Between Echinacea Purpurea & Cytochrome P450 Enzymes to strengthening Immunity to Resist Attacks by Microorganisms - Abdalla, Salem O.; Nagaah, Thabet A. (جامعة سرت - نقابة أعضاء هيئة التدريس, 2022)
تمتلك النباتات الطبية العديد من الأنشطة الدوائية التي لها تطبيقات هائلة في المجال الصيدلاني الحالي من أجل استكشاف الأدوية الطبيعية ذات الآثار الجانبية الأقل وأيضا التكلفة الأقل. أظهرت نتائج غرام البروتين وتركيز إشنيشابوربوريا عند 600 مجم/كجم / يوم و1 جم/كجم / يوم في نهاية الأسبوعين الثاني والرابع زيادة معنوية في جاما جلوب يولين من بين النباتات ذات الخصائص الدوائية وخصائصها. للتمتع الجمالي. وجد أنه يحتوي على منبهات مناعية، ومضاد للشماني، وسيتوكروم p450، ومبرمج-ومضاد للميكروبات. كما أنه فعال على الجسم المضاد واستجابة الخلايا المناعية وعلى علامات الشيخوخة ويمتلك القدرة الكاملة لمضادات الأكسدة. يحتوي على العديد من المركبات الكيميائية النباتية مثل الألاميداسوإسترات حمض الكافيك (حمض السيكوريك) والسكريات المتعددة والبولي أسيتيلين إلخ. في IgG في جميع المجموعات في نهاية الأسبوع الرابع وفي المجموعة B3 في نهاية الأسبوع الثاني والسادس. أظهر IgM زيادة معنوية في جميع المجموعات في نهاية الأسبوعين الثاني والرابع. كان النبات يستخدم تقليديا لعلاج التهابات الجهاز التنفسي، ولدغة الثعابين، وعلاج الأورام، والالتهابات وما إلى ذلك، وكان يستخدم بشكل خاص لتحفيز جهاز المناعة. Medicinal plants possess several pharmacological activities that have immense application in present pharmaceutical field in order to explore natural drugs of lesser side effects and also the lesser cost. Echinacea purpurea L. The protein gram results, concentration of Echinacea Purpurea at 600 mg/ kg/ day and 1 g/kg/day at the end of 2nd and 4th weeks revealed significant increase in gamma globulin is one among the plant with both pharmacological and the properties of the aesthetic enjoyment. It was found to contain immunostimulant, antileishmanial, cytochrome p 450, apoptotic - mitotic and anti-microbial activities. It also effective on antibody and immune cell response and on the markers of aging and possess total antioxidant capability. It has contained several phytochemical compounds such as alamedas, caffeic acid esters (cichoric acid), polysaccharides, polyacetylenes etc. In IgG in all groups at the end of 4th week and in group B3 at the end of 2nd and 6th week. IgM showed significant increase in all groups at the end of 2nd and 4th weeks. The plant was traditionally used for the treatment of respiratory infections, snake bite, tumor treatment, inflammation etc. and was particularly used for the stimulation of immune system.
Keywords: النباتات الطبية -- الأنشطة الدوائية -- الجهاز المناعي -- سيتوكروم P450